Blood-Brain Barrier Disruption Induced Cognitive Impairment Is Associated With Increase of Inflammatory Cytokine - Geng, Jieli; Wang, Liping; Zhang, Linyuan; Qin, Chuan; Song, Yaying; Ma, Yuanyuan; Chen, Yajing; Chen, Shengdi; Wang, Yongting; Zhang, Zhijun; Yang, Guo-Yuan (Frontiers in Aging Neuroscience, 2018)
Patients with diabetes suffer the higher risk of dementia and the underlying pathological mechanism of cognitive dysfunction in diabetes is not fully understood. In this study, we explore whether the cognitive impairment in the streptozotocin-induced diabetic rat is associated with increased BBB permeability and the change of the inflammatory cytokine. Experimental diabetic rats were induced by single intraperitoneal injection of streptozotocin (STZ). Cognitive function was evaluated by Morris water maze in the normal and the diabetic rats, respectively. The spatial acquisition trials were conducted over five consecutive days and the probe test was performed on day 6, followed by working memory test on the next 4 days. Escape latency was recorded in the acquisition trials and working memory test; time spent in the target quadrant and the number of crossing the former platform were recorded in the probe test. BBB permeability was assessed by measuring the extravasation of IgG. The image of occludin and claudin-5 staining by a confocal microscope were acquired to measure the gap in the tight junction. Cytokines TNF-α, IL-1β and IL-6 mRNA expression were further examined by Real-time PCR. The time spent in the target quadrant within 30 seconds decreased in the 8-week STZ rats compared to that of the normal rats (p < 0.05), while no difference was seen in the performance of working memory between the diabetic and normal rats. IgG leakage significantly increased in the brain parenchyma of the 8-week STZ rats compared to the normal rats (p < 0.05). The immunostaining of occludin and claudin-5 suggested the gap in the tight junction increased in the 8-week STZ rats compared to the normal rats (p < 0.05). Moreover, TNF-α and IL-6 mRNA also increased in the brain of 8-week STZ rats compared to the normal rats (p < 0.05). These results suggested that loss of BBB integrity might contribute to progressive impairment of cognitive in the diabetic rats. The increase of TNF-α and IL-6 expression might trigger the disruption of BBB in the brain, which eventually caused cognitive impairment in the 8-week STZ rats.